2021
DOI: 10.34172/ijhpm.2021.33
|View full text |Cite
|
Sign up to set email alerts
|

Implications of COVID-19: The Effect of Working From Home on Financial and Mental Well-Being in the UK

Abstract: In response to the threat posed by coronavirus disease 2019 (COVID-19), the UK prime minister announced on the 23rd of March strict lockdowns and introduced a new way of living and working, at least temporarily. This included working from home (WHF) wherever possible. Many experts from the IT industry were long arguing about the potential for WFH, which suddenly now became indisputable. The objective of this study is to evaluate the impact of WFH on the individuals’ perception about their future financial situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…It is noteworthy that some positive effects of working from home have been reported, such as increased productivity [31], improved mental well-being due to increased leisure time [38], greater level of flexibility in time management [65] which enables workers to better control and schedule their daily activities, more relaxation [39,65], and the reduced need to commute [24,65]. Furthermore, it should also be taken into account that the impact on mental well-being may depend on the frequency of working from home [66] and on whether it is mandatory or optional. Of note, in a survey study that evaluated the experience of 5748 workers from several different European countries who worked from home during the pandemic, the majority of workers reported a positive experience [67].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…It is noteworthy that some positive effects of working from home have been reported, such as increased productivity [31], improved mental well-being due to increased leisure time [38], greater level of flexibility in time management [65] which enables workers to better control and schedule their daily activities, more relaxation [39,65], and the reduced need to commute [24,65]. Furthermore, it should also be taken into account that the impact on mental well-being may depend on the frequency of working from home [66] and on whether it is mandatory or optional. Of note, in a survey study that evaluated the experience of 5748 workers from several different European countries who worked from home during the pandemic, the majority of workers reported a positive experience [67].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…[7] Similarly, whilst an analysis of the UK Household Longitudinal Study observed a decrease in mental well-being score during the pandemic for all adults sampled, they found a greater decrease amongst those who reported switching to home working constantly (as opposed to those who never worked at home). [30] In contrast however, a cross-sectional study of American adults found that switching to working from home was not associated with worsening of any of: depression; anxiety; stress; or positive mental health. [8] A rapid review which included papers published before and after lockdown [31] found that the evidence about the impact of homeworking on health (physical and mental) was conflicting: some studies found that home-working increased wellbeing while others found that it increased stress.…”
Section: Discussionmentioning
confidence: 93%
“…Pelly and colleagues 28 identified a general pattern of improved wellbeing in workers during the first full UK lockdown (May- July 2020), including reduced levels of exhaustion and negative emotions about work. Studies have primarily suggested positive effects of working from home 57 , with a few exceptions 8 , for example, Giovanis and Ozdamar 9 found home working during the pandemic was associated with poorer mental health compared to those working at employer’s premises, but only for full home working, not partial home working. More recent studies have suggested that impacts of home working on mental and social wellbeing during the pandemic have been especially strong among women and mothers 29,30 and keyworkers 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between home working and mental health is poorly understood, with mixed pre-pandemic evidence and potential mechanisms for both positive [5][6][7] and negative impacts 8,9 . Potential impacts of home working on health inequalities have been under-explored in the literature, so it is important to assess whether associations differ by social factors such as sex, age, education, and hours worked.…”
Section: Introductionmentioning
confidence: 99%